2021
DOI: 10.2174/2211352518999200429110222
|View full text |Cite
|
Sign up to set email alerts
|

Phytochemical Screening, Antimalarial, Antioxidant, Anti-inflammatory, and Antimicrobial Potential of Ananas comosus Extract

Abstract: Introduction: This study was undertaken to assess the antimicrobial, antioxidant, anti-inflammatory and antimalarial potential of fruit extract of Ananas comosus Linn. Bromelain is the major protease enzyme present in the pineapple. Methods: Screening of compounds using fluorescence-based assay was performed for antimalarial activity by Trager and Jenson method. Ethanolic extract of ananas cosmosus showed good antimalarial activity (EC50 = 1.94 ug/ml) as compared to the standard drug primaquine (EC50 = 0.0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…Additionally, the anti-inflammatory activity of the formulation at various concentrations (ranging from 10 to 50 µL) and diclofenac sodium was evaluated using this assay. The assay followed the methodology outlined by Kumar et al [ 17 ].…”
Section: Methodsmentioning
confidence: 99%
“…Additionally, the anti-inflammatory activity of the formulation at various concentrations (ranging from 10 to 50 µL) and diclofenac sodium was evaluated using this assay. The assay followed the methodology outlined by Kumar et al [ 17 ].…”
Section: Methodsmentioning
confidence: 99%
“…Various scientific studies reported that those ingredients in ALLURA™ possess antioxidant and anti-inflammatory activities. [3][4][5][6][7][8] Although the individual ingredient used in making ALLURA™ have been proven to possess therapeutic properties, the present study need to be conducted to validate the traditional claims, to justify its possible effectiveness thus supporting the scientifically validated knowledge of ALLURA™ ingredients.…”
Section: Introductionmentioning
confidence: 98%
“…antimalarial [8],anti-inflammatory [9], antidiabetic [10], anti-oxidant [11], anticancer [12] activities among others.This means that pineapple could be a valuable source of important bioactive compounds that have countlessbeneficial for therapeutic application.…”
Section: Introductionmentioning
confidence: 99%